Crl activates transcription by stabilizing active conformation of the master stress transcription initiation factor - Juncao Xu; Kaijie Cui; Liqiang Shen; Jing Shi; Lingting Li; Linlin You; Chengli Fang; Guoping Zhao; Yu Feng; Bei Yang; Yu Zhang (eLife, 2019)
σS is a master transcription initiation factor that protects bacterial cells from various harmful environmental stresses including antibiotic pressure. Although its mechanism remains unclear, it is known that full activation of σS-mediated transcription requires a σS-specific activator, Crl. In this study, we determined a 3.80 Å cryo-EM structure of an Escherichia coli transcription activation complex (E. coli Crl-TAC) comprising E. coli σS-RNA polymerase (σS-RNAP) holoenzyme, Crl, and a nucleic-acid scaffold. The structure reveals that Crl interacts with domain 2 of σS (σS2) and the RNAP core enzyme, but does not contact promoter DNA. Results from subsequent hydrogen-deuterium exchange mass spectrometry (HDX-MS) indicate that Crl stabilizes key structural motifs within σS2 to promote the assembly of the σS-RNAP holoenzyme and also to facilitate formation of an RNA polymerase–promoter DNA open complex (RPo). Our study demonstrates a unique DNA contact-independent mechanism of transcription activation, thereby defining a previously unrecognized mode of transcription activation in cells.